DIFICULTADES EN EL APRENDIZAJE DE LA MATEMÁTICA (Journal on studies and research of academic knowledge, 2008)
Difficulties in learning are those problems caused by the different ways the brain works and by the way it processes the information.Difficulties in Mathematics learning experienced by students are not by chance as they are based on their previous knowledge as well as on different reasons. So, these learning problems may be linked to didactic, epistemological, cognitive or attitudinal difficulties.Therefore, students with learning difficulties should experience plentiful and diverse situations, all of them related, in order to appreciate Mathematics, to develop mental habits, and to understand and appreciate its - portance in everyday life. In this context, e teacher plays an essential role in the knowledge building process. He/she becomes an active guide, responsible for the curriculum contextualization.Difficulties and errors are part of the knowledge building process and they may be a factor that causes changes in the student s ay of learning, becoming so, positive instruments for the teaching - learning process.
Keywords: Learning; Difficulties; Mathematics; Reasoning; Education; Student; Teacher; Process; Teaching; Building; Knowledge; Curriculum; Contextualization